Estimation of injury costs: financial damage of English Premier League teams' underachievement due to injuries. Issue 1 (20th May 2020) - Eliakim, Eyal; Morgulev, Elia; Lidor, Ronnie; Meckel, Yoav
Abstract : Background: In individual sports, the effect that injuries have on an athlete's performance, success and financial profit is implicit. In contrast, the effect of a single player's injury or one player's absence in team sports is much more difficult to quantify, both from the performance perspective and the financial perspective. Objectives: In this study, we attempted to estimate the effect of injuries on the performance of football teams from the English Premier League (EPL), and the financial implications derived from this effect. Methods: Our analysis is based on data regarding game results, injuries and estimations of the players' financial value for the 2012–2013 through the 2016–2017 seasons. Results: We found a statistically significant relationship (r=−0.46, 95% CI −0.6 to 0.28, p=0.001) between the number of days out due to injuries suffered by team members during a season and the place difference between their actual and expected finish in the EPL table (according to overall player value). Moreover, we can interpolate that approximately 136 days out due to injury causes a team the loss of one league point, and that approximately 271 days out due to injury costs a team one place in the table. This interpolation formula is used as a heuristic model, and given the relationship specified above accounts for a significant portion of the variance in league placement (21%), the remaining variance is related to other factors. Calculating the costs of wage bills and prize money, we estimate that an EPL team loses an average of £45 million sterling due to injury-related decrement in performance per season. Conclusion: Professional football clubs have a strong economic incentive to invest in injury prevention and rehabilitation programmes.